Detecting trace amount of water in crude oil with capacitance sensors - Tang, T.B. (Institute of Electrical and Electronics Engineers Inc., 2014)
A capacitive sensing system for trace amount of water content in crude oil is proposed. The capacitance sensor comprises a pair of copper electrodes wrapped around a tube with a 12mm diameter. The interface circuit is based on capacitance to phase angle conversion. A combination of differential sensing and low pass filtering techniques was further introduced to reduce the system sensitivity to jitter and amplitude variation in the main oscillator. Experiment results with Malaysia Dulang oilfield samples show that the proposed system has a sensitivity of 1.5Â°/fF and a detection range of 50 to 638ppm of water content. The system was able to produce a stable output (regular pulse stream without jitter). Â© 2014 IEEE.